Countdown to 2015: Status of MDG 5 in India and South Africa - A, Siruma; D, Hornby; S, Sunitha (Indian Journal of Pharmacy Practice)
The World Health Organization constitution declares that it is a fundamental right of every human being to enjoy the highest standard of health regardless of their racial, religious, and political or socio economic background. Challenges in not attaining the Alma Ata declaration by the year 2000 brought governments together in signing a Millennium Declaration at the 2000 Millennium Summit. Eight millennium development goals (MDGs) with time controlled targets to measure progress were listed. MDG 5 identified two targets for assessing progress in improving maternal health: reducing the maternal mortality ratio (MMR) by three-quarters between 1990 and 2015, and achieving universal access to reproductive health by 2015. The leading cause of maternal deaths worldwide is due to obstetric haemorrhage. Other direct causes of maternal deaths are due to ectopic pregnancy, embolism and causes related to use of anaesthetic. The World Health Organization (WHO) has recognised priority medicines for maternal health which form an essential constituent for combating maternal health complications. Sub-Saharan Africa and South Asia account for 84% of global maternal deaths, with haemorrhage as the leading cause of death in these regions. South Africa is a middle income country under the WHO Africa region, with a well-developed private sector and a stable macro-economy. Regrettably, South Africa appears amongst the 68 priority countries that have not made progress in reducing the maternal mortality rate since 1990. India, a lower middle income country also features amongst the 68 priority countries that have made insufficient progress in reducing their maternal mortality rate. With the countdown to 2015 drawing closer, the India and South Africa have a pressing obligation to take evocative steps to significantly decrease maternal mortality.
Keywords: Millennium development goal; maternal mortality; essential medicines; India; South Africa